Estimation of genetic parameters for visual score traits: a simulation study - Carreno, Luis Orlando Duitama [UNESP]; Ono, Rafael Keith [UNESP]; Utsunomiya, Adam Taiti Harth [UNESP]; Farah, Michel Marques [UNESP]; Cavani, Ligia [UNESP]; Silva, Danilo Pereira da [UNESP]; Harada, erik dos Santos [UNESP]; Fonseca, Ricardo da [UNESP] (Univ Federal Goias, 2025)
Visual scores are assigned with no basis on an absolute reference. In this case, evaluation references are different for each group, depending only on the structure of the group. Thus, factors that change the structure of evaluation groups, such as group size, can affect visual score assignment, as well as estimation of genetic parameters and prediction of breeding values, respectively. The objective of this study to determine the consequences of assigning scores based on a relative reference on the estimation of genetic parameters and breeding values considering different evaluation group sizes. A simulation study was conducted considering 6 scenarios formed by the combination of two populations (selected and unselected) and 3 group sizes (10, 40, and 100 animals) for evaluation. Genetic parameters and breeding values were estimated using two threshold models that differed in their correction for environmental effects. Heritability estimates for the two populations were close when the model corrected for environmental effects (0.407 - 0.418). However, heritability levels fell over generations when the model did not consider environmental effects (0.172 - 0.247). The size of the evaluation group mainly affected the accuracy of breeding values prediction, since higher accuracy was related to larger evaluation group sizes (0.576 - 0.715). We concluded that the way in which visual scores are assigned does not affect the estimation of genetic parameters and values. However, evaluation groups of more than 40 animals should be used to obtain greater accuracy and genetic progress.
Keywords: accuracy; environmental effects; heritability